2021
DOI: 10.3389/fpls.2021.749630
|View full text |Cite
|
Sign up to set email alerts
|

GhPLP2 Positively Regulates Cotton Resistance to Verticillium Wilt by Modulating Fatty Acid Accumulation and Jasmonic Acid Signaling Pathway

Abstract: Patatin-like proteins (PLPs) have non-specific lipid acyl hydrolysis (LAH) activity, which can hydrolyze membrane lipids into fatty acids and lysophospholipids. The vital role of PLPs in plant growth and abiotic stress has been well documented. However, the function of PLPs in plant defense responses against pathogens is still poorly understood. Here, we isolated and identified a novel cotton (Gossypium hirsutum) PLP gene GhPLP2. The expression of GhPLP2 was induced upon treatment with Verticillium dahliae, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 110 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…Especially, α-linolenic acid synthesis was downregulated. Linolenic acid was the precursor of jasmonic acid (JA), and JA is a lipogenic plant hormone that regulates the defensive responses of plants to biological and abiotic stresses (Zhao et al, 2014;Balfagon et al, 2019;Zhu et al, 2021;Pyo et al, 2022). Downregulated linolenic acid may suggest that stress levels in potato plants of group CC1 were not increased very much compared to that of group CC0.…”
Section: Metabolic Pathways In Potato Controlling Root Exudates Affec...mentioning
confidence: 99%
“…Especially, α-linolenic acid synthesis was downregulated. Linolenic acid was the precursor of jasmonic acid (JA), and JA is a lipogenic plant hormone that regulates the defensive responses of plants to biological and abiotic stresses (Zhao et al, 2014;Balfagon et al, 2019;Zhu et al, 2021;Pyo et al, 2022). Downregulated linolenic acid may suggest that stress levels in potato plants of group CC1 were not increased very much compared to that of group CC0.…”
Section: Metabolic Pathways In Potato Controlling Root Exudates Affec...mentioning
confidence: 99%
“…In recent years, efforts have been made to manipulate key fatty acid synthetic genes in various species using transgenic technology [43][44][45][46][47]. Transformations using transgenes encoding key enzymes or enzyme subunits have resulted in the alteration in lipid levels to varying degrees [37,48], and in some cases, the oil content was reduced [49]. Four key enzymes were involved in the fatty acid carbon-chain extension process, namely KAS, KAR, HAD, and ENR.…”
Section: The Application Of Fatty Acid Synthase In Improving Seed Oil...mentioning
confidence: 99%
“…In our study, transcriptome analysis revealed that a significant number of DEGs was enriched in the "plant hormone signaling" pathway when comparing non-treated and salt-treated RIL pur-W22 and RIL bro-W22 seedlings. Additionally, through KEGG pathway enrichment analysis, we observed the enrichment of precursor synthesis or metabolic pathways related to various plant hormones [48][49][50][51]. For instance, the "tryptophan biosynthesis" pathway is associated with auxin, the "methionine metabolism" pathway corresponds to ethylene, the "carotenoid synthesis" pathway is related to abscisic acid (ABA), and the "linoleic acid metabolism" pathway is correlated with jasmonic acid (Jas) (Figure S3).…”
Section: The Salt Stress Tolerance In Maize Seedlings May Be Mediated...mentioning
confidence: 99%